2019
DOI: 10.36740/wlek201904106
|View full text |Cite
|
Sign up to set email alerts
|

Features of Clinical Manifestations, Free Radical, Coagulation and Aggregation Properties of Blood in Patients With Craniocerebral Trauma

Abstract: Introduction: In recent years in Ukraine, as in the entire world, there has been an increase in cases of domestic injuries with a raise in the number of patients with craniocerebral trauma and its consequences. The aim of our research was to study clinical symptoms, the state of free radical oxidation, aggregate and hemocoagulative properties of blood in patients with mild craniocerebral trauma. Materials and methods: We conducted comprehensive clinical and laboratory examination of 34 patients with mild crani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The injury of patients with craniocerebral trauma is related to hematoma, and the intracranial pressure can lead to the patient's disturbance of consciousness or coma [ 6 ]. The common complications of severe craniocerebral injury mainly refer to the complications of other parts except the craniocerebral injury itself.…”
Section: Related Workmentioning
confidence: 99%
“…The injury of patients with craniocerebral trauma is related to hematoma, and the intracranial pressure can lead to the patient's disturbance of consciousness or coma [ 6 ]. The common complications of severe craniocerebral injury mainly refer to the complications of other parts except the craniocerebral injury itself.…”
Section: Related Workmentioning
confidence: 99%
“…Craniocerebral trauma is one of the common emergency departments of brain surgery, and its clinical symptoms are head trauma, hemorrhage, intracranial hypertension and disturbance of consciousness caused by trauma [ 1 , 2 ]. The brain tissue damage of the patient causes the nervous system function to be affected, which affects the cognitive ability, motor function, and inconvenience to daily life [ 3 , 4 ]. Early full nursing for some patients with dysfunction is helpful to accelerate the reorganization of central nervous system function and coordinate muscle and limb activities [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, it has been found out that in periodontitis in the blood of patients there is an accumulation of LPO products due to a significant increase in the level of malonic dialdehyde with a decrease in the concentration of superoxide dismutase and catalase [6,7]. The results of the study of total antioxidant activity showed that the values of this parameter in the tissues of the gums in cases of intact periodontitis and generalized periodontitis have significant differences [8,9].…”
Section: Introductionmentioning
confidence: 99%